Short-term Indicator Models for Quarterly GDP Growth in the BRIICS A Small-scale Bridge Model Approach - Chalaux, Thomas (OECD Economics Department Working Papers, 2014)
This paper extends the OECD Economics Department's suite of short-term indicator models for quarterly GDP growth, which currently cover only the G7 countries, to the BRIICS countries. Reflecting the relative scarcity of high-quality macroeconomic time series, the paper adopts a small-scale bridge model approach. The results suggest that in terms of short-term forecast accuracy for the first and second quarter following the most recent GDP release these models outperform simple autoregressive or constant growth benchmarks. The small-scale indicator models would have allowed the identification of the growth slowdown during the global crisis of 2008-09 and the subsequent rebound several months ahead of official GDP releases. Overall, forecast accuracy appears to be similar to that of the existing indicator model suite for the G7 countries, especially once the higher GDP growth volatility in most BRIICS is accounted for